Solve the non-homogeneous differential equation below.
⎩ ⎪ ⎨ ⎪ ⎧ y ′ ′ + 1 0 y ′ + 2 9 y = 3 5 3 8 ( sin ( 2 t ) cos ( 2 t ) + cos 2 ( 2 t ) − sin 2 ( 2 t ) ) y ( 0 ) = − 1 6 y ′ ( 0 ) = 3 8 6
If y ( 2 π ) = A e A B π − 7 A , where A and B are integers, enter A B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The partial solution to the homogeneous form of the differential equation is given by:
y " + 1 0 y ′ + 2 9 y ( r 2 + 1 0 r + 2 9 ) e r x ⟹ r = 0 = 0 = − 5 ± 2 i where i = − 1 is the imaginary unit.
⟹ y 1 ( x ) = c 1 e − 5 x sin 2 x + c 2 e − 5 x cos 2 x where c 1 and c 2 are constants.
Since y " + 1 0 y ′ + 2 9 y = 3 5 3 8 ( sin 2 x cos 2 x + cos 2 2 x − sin 2 2 x ) = 1 7 6 9 sin 4 x + 3 5 3 8 cos 4 x , assuming the special solution be y 2 ( x ) = C sin 4 x + D cos 4 x , where C and D are constants. Then y 2 ′ = 4 C cos 4 x − 4 D sin 4 x , y 2 ′ ′ = − 1 6 C sin 4 x − 1 6 D cos 4 x = − 1 6 y 2 , and
y 2 ′ ′ + 1 0 y 2 ′ + 2 9 y 2 1 0 ( 4 C cos 4 x − 4 D sin 4 x ) + 1 3 ( C sin 4 x + D cos 4 x ) = 1 7 6 9 sin 4 x + 3 5 3 8 cos 4 x = 1 7 6 9 sin 4 x + 3 5 3 8 cos 4 x
Equating the coefficients on both sides:
{ 1 3 C − 4 0 D = 1 7 6 9 4 0 C + 1 3 D = 3 5 3 8 ⟹ C = 9 3 , D = − 1 4 ⟹ y 2 ( x ) = 9 3 sin 4 x − 1 4 cos 4 x
Therefore the general solution of the differential equation is:
y ( x ) ⟹ y ( 2 π ) = c 1 e − 5 x sin 2 x + c 2 e − 5 x cos 2 x + 9 3 sin 4 x − 1 4 cos 4 x = − c 2 e − 2 5 π − 1 4 As y ( 0 ) = c 2 − 1 4 = − 1 6 ⟹ c 2 = − 2 = 2 e − 2 5 π − 1 4
Therefore A B = ( 2 ) ( − 5 ) = − 1 0 .
Problem Loading...
Note Loading...
Set Loading...
Solving the given differential equation we get y = 9 3 sin 4 t − 1 4 cos 4 t + A e − 5 t sin ( 2 t + α ) , where A and α are constants of integration. Substituting the initial conditions we get A = 2 2 , α = − 4 π . Hence y ( 2 π ) = − 1 4 + 2 e − 2 5 π . So A = 2 , B = − 5 and A B = − 1 0 .